Pengaruh Profitabilitas, Aset Pajak Tangguhan, Pajak Kini dan Perencanaan Pajak terhadap Manajemen Laba - Nur Hasanah, Alifa Shafiya; Indra Pahala; Unggul Purwohedi (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
The study's goal was to examine how profitability, deferred tax assets, current tax expenses, and tax planning affect profit management. The population for the study was made up of property and real estate companies listed on the Indonesian Stock Exchange (IDX) from 2020 to 2022. This study method used a quantitative method with data in the form of financial reports available on the IDX website. Samples selected using purposive sampling techniques and produced 66 observational data. Data is processed using SPSS applications and analyzed using logistic regression analysis. This research uses secondary data taken from the company's financial statements. Based on the analysis of this study, it is possible to conclude that the current tax expense has a positive and significant influence on profit management, profitability has a negative and significant influence on profit management, and deferred tax assets and tax planning are not significant to profit management.